Epidemiology of cardiovascular risk factors in Greece: aims, design and baseline characteristics of the ATTICA study - Chrysohoou Christina; Panagiotakos Demosthenes B; Pitsavos Christos; Stefanadis Christodoulos (BMC, 2003)
Abstract Background In an attempt to evaluate the levels of several cardiovascular risk factors in Greece we conducted a population-based health and nutrition survey, the "ATTICA study". In this work we present the design and the methodology of the study, as well as the status of various baseline characteristics of the participants. Methods From May 2001 to December 2002 we randomly enrolled 1514 adult men and 1528 adult women, stratified by age - gender (census 2000), from the greater area of Athens. More than 300 demographic, lifestyle, behavioral, dietary, clinical and biochemical variables have been recorded. Results Regarding the frequency of the classical cardiovascular risk factors we observed that 51% of men and 39% of women reported smokers (p < 0.05), 37% of men and 25% of women were defined as hypertensives (p < 0.05), 46% of men and 40% of women had total serum cholesterol levels above 200 mg/dl (p < 0.05) and 8% of men and 6% of women had history of diabetes mellitus. Moreover, 20% of men and 15% of women were obese (p < 0.05), while men were more physically active as compared to women (42% vs. 39%, p < 0.05). 19% of men and 38% of women had mild to severe depressive symptoms (p < 0.01). Finally, 72 men (5%) and 45 (3%) women reported history of coronary heart disease at entry evaluation. Conclusions The prevalence of the common cardiovascular risk factors in our population seems high. As a consequence a considerable proportion of Greek adults are at "high-risk" for future cardiovascular events.